Biofunctional Nanodot Arrays in Living Cells Uncover Synergistic Co‐Condensation of Wnt Signalodroplets (Small 50/2022). Issue 50 (15th December 2022) - Philippi, Michael; Richter, Christian P.; Kappen, Marie; Watrinet, Isabelle; Miao, Yi; Runge, Mercedes; Jorde, Lara; Korneev, Sergej; Holtmannspötter, Michael; Kurre, Rainer; Holthuis, Joost C. M.; Garcia, K. Christopher; et al.
Abstract : Wnt Signalodroplets High‐density arrays of biofunctionalized nanodots with diameters of 300 nm enable spatially controlled assembly of active Wnt signaling platforms in the plasma membrane. Massive parallelization at the single cell level uncovers receptor density‐dependent co‐condensation of cytosolic effector proteins, suggesting a digitalized transmembrane signaling controlled by liquid–liquid phase separation. More details can be found in article number 2203723 by Martin Steinhart, Jacob Piehler, Changjiang You, and co‐workers.